Idiopathic hirsutism – medical and psychological aspects - Jarząbek-Bielecka, Grażyna; Warchoł-Biedermann, Katarzyna; Kędzia, Witold (Journal of Medical Science, 2014)
Introduction. Hirsutism is a condition which results in excess of male pattern hair growth - the androgen dependent hair in females. Excessive hair growth usually starts around puberty. The aim of this study was to show the significance of hormonal diagnosis in female adolescent hirsute patients.Material and methods. The material consisted of medical documentation of 128 female adolescent patients aged 13–22 years who came for a consultation because of excessive male pattern hair growth (second degree of hirsutism according to the Ferriman-Gallwey scale) which they considered unacceptable. The history was indicative of considerable discomfort, decreased mood in subjects and low self-esteem (especially regarding patient’s femininity).Results. Results of the analysis were confronted with the results of a group of an equal number of participants.Conclusions. Hormonal tests in female patients with hirsutism were proven to constitute a major diagnostic element allowing for correct diagnosis of the cause of hirsutism, planning further tests and treatment methods.Considering its causes and effects, hirsutism in adolescent patients is a serious concern for developmental gynecology. This disorder is a endocrinological or gynecological problem, which influences patient's well-being.
Keywords: hair; gynecology; sexuology; girl; women